Food safety in India: a case of Deli Processed Food Products Ltd. (1st January 2014) - Mahajan, Rajneesh; Garg, Suresh; Sharma, P.B.
Food safety issues are becoming more important in India. It is not because of global pressure of the World Trade Organization (WTO), a monitoring agency in this respective field, it is because of customers' increasing demand for better quality food. The Food Safety Standards Authority of India (FSSAI) came into existence under Food Safety and Standards Act, 2006. It covers all the global food safety norms laid down by WTO such as goods manufacturing practices (GMP), good hygienic practice (GHP), and hazard analysis critical control point (HACCP). This paper illustrates implementation of HACCP, food safety controls and its status in India using a case study of Deli Processed Food Products Ltd. (DPFPL, organisation's name is disguised) which deals in milk processing and milk products production in India.